1987
DOI: 10.1190/1.1442378
|View full text |Cite
|
Sign up to set email alerts
|

A case for upward continuation as a standard separation filter for potential‐field maps

Abstract: Separation filtering is incomplete even under the ideal synthetic condition of known power spectra of the regional and residual fields. I have designed some Wiener filters, which minimize the inevitable separation error, from previous statistical source models of Naidu, and Spector and Grant. This formulation includes the classic separation filters of Strakhov and of Elkins as Wiener filters. A proposed generalization of Wiener filters, denoted as uniformly suboptimum filters, quantitatively supports the state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
174
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 370 publications
(177 citation statements)
references
References 11 publications
0
174
0
3
Order By: Relevance
“…It has a maximum at the altitude h 0 , corresponding to the optimal altitude of upward continuation of the Bouguer in the region. As such, the upward of the Bouguer to the altitude h 0 serves to eliminate the gravity related effect of the sources located beyond the altitude h 0 /2 which is the depth whose anomalies constitute a residual field [25].…”
Section: Methodsmentioning
confidence: 99%
“…It has a maximum at the altitude h 0 , corresponding to the optimal altitude of upward continuation of the Bouguer in the region. As such, the upward of the Bouguer to the altitude h 0 serves to eliminate the gravity related effect of the sources located beyond the altitude h 0 /2 which is the depth whose anomalies constitute a residual field [25].…”
Section: Methodsmentioning
confidence: 99%
“…Spectral analysis is a technique widely used in gravity analysis to design filters that make it possible to obtain regional trends and eliminate short wavelength signals produced by shallow sources. Upward continuation is one of the most effective filtering techniques for potential field maps in the frequency domain (Jacobsen, 1987;Blakely, 1995). This transformation attenuates anomalies with respect to wavelength; the shorter the wavelength, the greater the attenuation.…”
Section: Methodsmentioning
confidence: 99%
“…This depth is fixed by optimum upward continuation height h 0 . Indeed, on the basis of a model of basement made up of an assembly of thin layers, [44] showed that the power spectrum of regional and residual fields can be expressed in the form of:…”
Section: Estimation Methods Of the Investigation Depthmentioning
confidence: 99%